Recyclable Cu(II)-(MAA-EGDMA) catalyst for selective oxidation of alcohols to aldehydes using sodium hypochlorite - Khojasteh, Roya Ranjineh; Maleki, Mitra (European Journal of Chemistry, 2020)
Copper(II) α-benzoin oxime complex was synthesized by the reaction between copper(II) benzoate and α-benzoin oxime. The poly methacrylic acid-ethylene glycol dimethacrylate (MAA-EGDMA) was applied as support of copper complex catalyst for oxidation of alcohols to aldehydes using NaClO. The structure and morphology of immobilized Cu(II)-benzoin oxime have been studied by using different analysis including Fourier Transform Infrared (FT-IR) spectroscopy, Scanning Electron Microscopy (SEM) and Thermal Gravimetric Analysis (TGA). The yield of aldehydes was determined by Gas Chromatography (GC) analysis. The immobilized Cu(II)-benzoin oxime indicated a high catalytic activity compared to its absence for the alcohol oxidation with sodium hypochlorite. The effect of the reaction time and temperature, the solvent type, the amounts of catalyst and NaClO were optimized to obtain maximum yield. The prepared catalyst had various benefits such as being inexpensive, environmentally friendly manner, recyclable, reducing the reaction time and increasing the yield. A reaction mechanism is proposed for oxidation of alcohols in the presence of the catalyst.